Saddle and nodal point impact on magnetohydrodynamic stagnation-point flow of Casson nanofluid flow toward Howarth's wavy circular cylinder (Journal of Naval Architecture and Marine Engineering, 2024)
Casson fluid flow helps us understand and model fluids that do not follow Newton's law of viscosity. Many real-world fluids, such as blood, ketchup, paints, and various biological fluids, exhibit non-Newtonian behaviour. The present exploration presents the numerical investigation of a Casson nanofluid flow's MHD stagnation-point flow over Howarth's wavy circular cylinder. The coupled nonlinear ODE is generated from a nonlinear partial differential equation with the use of similarity transformations. After that, the MATLAB software's built-in bvp4c is used for the numerical solution of the nonlinear system. The pertinent governing parameters impact on temperature, velocity and concentration profiles are examined through graphs. Numerical values of physical quantities such as friction coefficient in x and y directions, diffusion mass flux, and local Nusselt number are employed. The influence of Casson parameter stabilizes the momentum boundary layer growth on axial velocity and radial velocity profiles and reduced the thermal and concentration boundary layer.Journal of Naval Architecture and Marine Engineering, 21(2), 2024, P: 103-116